PIT Design Area 206 Ha at PT Semen Padang Indarung - Riri Rahmahwati Joni; Aldri Frinaldi; Rembrandt Rembrandt; Dasman Lanin; Genius Umar (Science and Environmental Journal for Postgraduate, 2022)
PT. Semen Padang is a mining company engaged in quarry (limestone) mining. The company is located in Bukit Karang Putih – Indarung, Padang City. Mining in this company uses the Type Side Hill Quarry system. For production in the 206 Ha mining area using a combination of mechanical devices in the form of Excavators and Dump Trucks. With supporting tools in the form of a D9R Bulldozer and a GC-02 Motor Grader. The target of this activity is to optimize mining production in the 206 Ha pit area. Efforts were made to optimize mining production in the Exit Area and PIT Limit from 2014 – 2016 by combining Excavator and Dump Truck mechanical devices to the crusher loading area with a volume of 24,872,835 tons, 28,304,505 tons and 26,029,609 tons. Whereas in 2017 – 2020 only the PIT Limit area will carry out mining production, this is because the reserves in the Existing area have run out. PIT Limit production from 2017 – 2020 is 21,864,874 tons, 20,981,407 tons, 20,831,837 tons, and 20,662,775 tons.